Epidemiological and ES cell‐based functional evaluation of BRCA2 variants identified in families with breast cancer. Issue 2 (31st December 2020) - Sullivan, Teresa; Thirthagiri, Eswary; Chong, Chan‐Eng; Stauffer, Stacey; Reid, Susan; Southon, Eileen; Hassan, Tiara; Ravichandran, Aravind; Wijaya, Eldarina; Lim, Joanna; Taib, Nur Aishah Mohd; Fadzli, Farhana; et al.
Abstract: The discovery of high‐risk breast cancer susceptibility genes, such as Breast cancer associated gene 1 (BRCA1) and Breast cancer associated gene 2 (BRCA2) has led to accurate identification of individuals for risk management and targeted therapy. The rapid decline in sequencing costs has tremendously increased the number of individuals who are undergoing genetic testing world‐wide. However, given the significant differences in population‐specific variants, interpreting the results of these tests can be challenging especially for novel genetic variants in understudied populations. Here we report the characterization of novel variants in the Malaysian and Singaporean population that consist of different ethnic groups (Malays, Chinese, Indian, and other indigenous groups). We have evaluated the functional significance of 14 BRCA2 variants of uncertain clinical significance by using multiple in silico prediction tools and examined their frequency in a cohort of 7840 breast cancer cases and 7928 healthy controls. In addition, we have used a mouse embryonic stem cell (mESC)‐based functional assay to assess the impact of these variants on BRCA2 function. We found these variants to be functionally indistinguishable from wild‐type BRCA2. These variants could fully rescue the lethality of Brca2 ‐null mESCs and exhibited no sensitivity to six different DNA damaging agents including a poly ADP ribose polymerase inhibitor. Our findings strongly suggest that all 14 evaluated variants are functionally neutral. Our findings should be valuable in risk assessment of individuals carrying these variants.